ИСТОРИЧЕСКАЯ РЕАЛЬНОСТЬ И СОЧЕТАНИЕ ПАФОСА В ЖАНРЕ ТЕТРАЛОГИЯ - Яхшиева, З. (SCIENCE and SOCIETY, 2021)
It is known that in order to turn historical truth into an artistic reality, a writer requires a lot of creative research, careful study of the imaginative, factual materials. The concept of pathos, which creates and coordinates the poetic idea, becomes clear. Indeed, as a result of many years of creative research, Muhammad Ali's tetralogy "Great Power", which came to the world, is a typical example of this process. Artistic pathos is part of the artistic style. It displays a lyric-romantic mood. Creative ideas and imagination of the writer are inextricably linked with Pathos. It is theoretically proved that this aspect is related to the meaningful field of tetralogy.
Keywords: pathos; tetrology; novel form; dynasties; epic novel